Passer d’un modèle de fonctionnement associatif à un modèle institutionnel : une analyse des transformations de l’organisation du travail - Lysianne Rochat; Viviane Gonik; Brigitta Danuser (Perspectives Interdisciplinaires sur le Travail et la Santé)
In recent decades, the context of humanitarian aid has undergone many developments involving changes in the means of operation of aid organizations. We conducted a study at the headquarters of an NGO, in which we collected data via a questionnaire, semi-structured interviews and activity analyses. We identified the elements implemented in the process of the professionalization of the management structure and how they were perceived by the employees. Numerous aspects of the associative ideal remain strong in the organization. Resistance against formal management exists, which leads to the cohabitation of these two ways of functioning which we called associative and institutional. Shifts resulting from this cohabitation create a particular mode of organization and generate paradoxical messages for the employees, which may have impacts on their health.